Analisis Perancangan Sistem Manajemen Payroll Menggunakan Metode Agile Berbasis Web (Studi Kasus PT. JBM Bio Energy) - Simatupang, Rentauli; Adi Lukito, Surya (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This study aims to design a web-based payroll management system using the Agile method, with a case study at PT. JBM Bio Energy. The system is designed to address issues in payroll data management, which has been done manually, prone to errors, and time-consuming. The Agile method is applied to ensure the system development process is iterative and adaptive to user needs. The system includes key features such as employee data management, automated payroll calculations, recording of deductions and allowances, and report generation. The results of this study indicate that the designed system can improve efficiency and accuracy in the company's payroll management. By implementing this system, PT. JBM Bio Energy is expected to optimize payroll administration processes and support data-driven decision-making.